Exploratory Study on the Moral Development of Adolescent Premarital Sex Actors: Exploratory Study on the Moral Development of Adolescent Premarital Sex Actors - Gita Fahmi Lestari; Indah Sukmawati; Nurdewi Azizah Safitri; Megawati Simanjuntak; Yulina Eva Riany (Journal of Family Sciences, 2022)
Premarital sexual behavior among teenagers is getting higher. The low level of moral education and failure in the division of roles, functions, and duties in the family triggers adolescents to behave freely and even violate religious and social norms. This research was conducted to look at the description of moral development and the factors that cause adolescents to have premarital sex. This study uses a qualitative method with a phenomenological research design with a purposive sampling technique. The research was conducted in Bogor Regency. Respondents in this study were teenage girls and boys and their biological mothers, totaling four people. This study indicates that all participants feel that the moral education they have received so far is not understood and even applied in everyday life. Teenagers have understood premarital sex behavior but have a different interpretation of it. This is due to several factors that cause teenagers to have premarital sex, such as lack of attention from parents, failure of family functions, lack of moral and character education, and environmental influences.